2019
DOI: 10.1111/ele.13402
|View full text |Cite
|
Sign up to set email alerts
|

Polyploid plants have faster rates of multivariate niche differentiation than their diploid relatives

Abstract: Polyploid speciation entails substantial and rapid postzygotic reproductive isolation of nascent species that are initially sympatric with one or both parents. Despite strong postzygotic isolation, ecological niche differentiation has long been thought to be important for polyploid success. Using biogeographic data from across vascular plants, we tested whether the climatic niches of polyploid species are more differentiated than their diploid relatives and if the climatic niches of polyploid species different… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
111
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(112 citation statements)
references
References 156 publications
(174 reference statements)
1
111
0
Order By: Relevance
“…Presently, our results provide a testable hypothesis to explain the observed correlation of polyploidy and crop domestication 10 .More broadly, our results suggest that paleopolyploidy may leave behind a legacy of elevated genetic diversity across the duplicated remnants of diploidized genomes. Although most models and studies of polyploid evolution compare diploids and polyploids11,12,14,16,17,19,[70][71][72] , our comparison of paleologs and non-paleologs within a diploidized paleopolyploid uncovered evidence for similar dynamics ongoing within plant genomes even millions of years after whole genome duplication. The extensive genome duplication history of plants may result in genomes with different levels of diversity based on the mechanisms of gene origin.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Presently, our results provide a testable hypothesis to explain the observed correlation of polyploidy and crop domestication 10 .More broadly, our results suggest that paleopolyploidy may leave behind a legacy of elevated genetic diversity across the duplicated remnants of diploidized genomes. Although most models and studies of polyploid evolution compare diploids and polyploids11,12,14,16,17,19,[70][71][72] , our comparison of paleologs and non-paleologs within a diploidized paleopolyploid uncovered evidence for similar dynamics ongoing within plant genomes even millions of years after whole genome duplication. The extensive genome duplication history of plants may result in genomes with different levels of diversity based on the mechanisms of gene origin.…”
mentioning
confidence: 88%
“…Analyses in yeast have shown that polyploid lineages not only have higher genetic diversity but also adapt to new environments faster than their lower ploidal level relatives 16 . Similarly, the niches of polyploid plants evolve faster than their diploid relatives 17 . These features may collectively give polyploids unique advantages over diploids during domestication and the global spread of crops that occurred with human population expansion.…”
Section: Introductionmentioning
confidence: 99%
“…Despite recent work using ecological modelling across species to address the success of polyploids (e.g. Martin & Husband 2009;Glennon et al 2014;Marchant et al 2016;Baniaga et al 2019), the evolution of their ecological niches following the combination of diploids remains elusive. To account for the impact of hybridisation between differentially adapted taxa, Parisod & Broennimann (2016) suggested to not only rely on adequate phylogenies but to go beyond ambiguous pairwise comparisons by testing the null hypothesis that allopolyploids represent the additivity of their diploid progenitors.…”
Section: Introductionmentioning
confidence: 99%
“…Many questions in ecology and evolutionary biology increasingly require combining data from these fields at large scales. In particular, integrated, large-scale analyses of multispecies ecological and phylogenetic data sets have become critical to understanding plant distributions and responses to climate change (Zanne et al, 2014;Swenson and Jones, 2017;Maitner et al, 2018;Enquist et al, 2019;Gallagher et al, 2019;McFadden et al, 2019;Rice et al, 2019;Baniaga et al, 2020;RomĂĄn-Palacios and Wiens, 2020) . Recognizing this need, NSF recently launched the National Ecological Observatory Network (NEON) to generate large-scale data on species occurrence, phenology, climate, and more, for ecological communities across the United States (Collinge, 2018;Knapp and Collins, 2019) .…”
Section: Introductionmentioning
confidence: 99%